GATA3: Orchestrating cellular fate through differentiation and proliferation - Rim Bacha (14779420) (2024)
Cell proliferation and differentiation are two fundamental biological processes that occur in biological systems, tightly regulated by various factors such as transcription factors (TFs). Zinc finger proteins are TFs responsible for maintaining the biological balance via coordinating development and functionality within the living cells. GATA binding protein 3 (GATA3), one of the zinc finger proteins, plays an essential role in driving differentiation and proliferation-related processes, thereby contributing to the regulation of the dynamism and productivity of living cells. By elucidating the complex interactions governed by GATA3, this underscores its significance in maintaining cellular homeostasis. Thus, the current review delves into the molecular pathways influenced by GATA3, highlighting its involvement in multiple developmental processes of various tissues and body sites, particularly in the hematopoietic system (T-cell differentiation), neural tissue differentiation, adipose tissue, as well as epithelial cell maturation. Other Information Published in: Biochimica et Biophysica Acta (BBA) - Molecular Cell Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bbamcr.2024.119893